Optimizing the Role of the Community in Community Empowerment Through Out of School Education - Wedi Fitriana (Empowerment : Jurnal Ilmiah Program Studi Pendidikan Luar Sekolah, 2018)
Society is a social group that also has enormous potential if it can direct its ability to develop various competencies that can provide added value in their lives. The problem is the role of the community, often because of ignorance of the problems of their own lives. Therefore, it is necessary to develop a series of out-of-school education programs that are far more comprehensive in order to build public awareness to be involved in a far more optimal process of community empowerment.